Critical Thinking in Problem Exploration in Design and Technology Design Project - LOH, Wei Leong Leon (Design and Technology Education: An International Journal, 2020)
The current study aimed to identify and clarify students’ critical thinking processes in problem exploration. The current study will adopt the definitions of critical thinking conceptualized by Paul and Elder and, at the same time, attempt to apply the concept of elements of reasoning and intellectual standards to achieve the objectives of this study. By using questions to deconstruct the elements of reasoning when exploring problems, the intellectual standards for reasoning in problem exploration can be articulated. Using a qualitative approach to conduct a collective case study, 15 design journals completed by students in the upper secondary Express course in Singa Secondary School are used as objects of study. The primary source of data is collected via the documentations in the design journals. Using intellectual standards for reasoning in problem exploration to interpret the documentations in the design journals, students’ quality of reasoning can be observed and consolidated. Based on the findings, the following conclusion can be presented. Firstly, to achieve depth, accuracy and unbiased understanding of the problem, students need to research on information and data from different sources to triangulate the problem. Secondly, it is necessary for students to acquire necessary background knowledge in order to conceptualize problems accurate and clearly. Thirdly, the development of intellectual standards for reasoning relevant to the design process in D&T may be a potentially useful strategy for teachers to explicitly develop critical thinking skills in D&T.